2010
DOI: 10.1117/12.853710
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence enhancement of semiconducting-carbon-nanotubes-based thin films

Abstract: Semiconducting single wall carbon nanotubes (s-SWNT) are unique monodimensional material of particular interest in photonics for their direct band-gap, allowing tunable near-IR luminescence from electron-hole recombinaison. However, the presence of metallic nanotubes and impurities in real carbon nanotubes samples creates several non radiative relaxation mechanisms, leading to an effective quenching of s-SWNT photoluminescence and limiting their usability in photonics devices. Recently, we have developed a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…While the aryl functionalization described in Section 3.2 efficiently activates such dark excitonic state, it still degrades the crystalline structure of the tubes. To escape this boundary, SWNTs have been embedded in special optical environments such as cavities [162], [163] or photonic crystals [164] to exploit their ad-hoc designed electromagnetic modes. Another suitable approach comprises plasmons, the special electromagnetic modes arising from the collective free-electrons oscillations in metals and localized close to the metal surface.…”
Section: Nanoplasmonic Hybridizationmentioning
confidence: 99%
“…While the aryl functionalization described in Section 3.2 efficiently activates such dark excitonic state, it still degrades the crystalline structure of the tubes. To escape this boundary, SWNTs have been embedded in special optical environments such as cavities [162], [163] or photonic crystals [164] to exploit their ad-hoc designed electromagnetic modes. Another suitable approach comprises plasmons, the special electromagnetic modes arising from the collective free-electrons oscillations in metals and localized close to the metal surface.…”
Section: Nanoplasmonic Hybridizationmentioning
confidence: 99%
“…Previously reported light emission enhancement from nanotubes was by embedding a layer of CNT-PFO between two dielectric mirrors, formed by a SiO 2 /Si 3 N 4 multilayer-stack, which created a Fabry-Perot cavity and resulted in reinforced light emission [25]. A more clear demonstration later in a silicon 2D photonic cavity [14] has shown that CNTs PL emission is largely enhanced with sharp resonance peaks when CNTs are placed in or near cavity centre, otherwise no resonance emission peaks for off cavity can appear.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanotube thin films and their subsequent integration into photonic devices was seldomly studied, with few results. 23,24 In fact, while s-SWNT individually displays very strong photonic properties, metallic carbon nanotubes (m-SWNT), catalytic impurities and bundled s-SWNT remaining in samples quenches photoluminescence by non radiative desexcitation paths, from m-SWNT interactions or s-SWNT exciton transfert. 25,26 The extraction of s-SWNT is a real challenge, and in recent years, several approachs to extract them from nanotube powders have been explored, using for instance chemical functionalization, DNA, polymers wrapping and density gradient ultracentrifugation techniques.…”
Section: Introductionmentioning
confidence: 99%